Quantifying the extent of calcification of a coccolithophore using a coulter counter - Fan, X; Batchelor-McAuley, C; Yang, M; Barton, S; Rickaby, REM; Bouman, HA; Compton, RG (American Chemical Society, 2022)
Although, in principle, the Coulter Counter technique yields an absolute measure of particle volume, in practice, calibration is near-universally employed. For regularly shaped and non-biological samples, the use of latex beads for calibration can provide sufficient accuracy. However, this is not the case with particles encased in biogenically formed calcite. To date, there has been no effective route by which a Coulter Counter can be calibrated to enable the calcification of coccolithophores─single cells encrusted with biogenic calcite─to be quantified. Consequently, herein, we seek to answer the following question: to what extent can a Coulter Counter be used to provide accurate information regarding the calcite content of a single-species coccolithophore population? Through the development of a new calibration methodology, based on the measurement and dynamic tracking of the acid-driven calcite dissolution reaction, a route by which the cellular calcite content can be determined is presented. This new method allows, for the first time, a Coulter Counter to be used to yield an absolute measurement of the amount of calcite per cell.